Evaluating Corporate Social Responsibility Implementation: The MSME Canteen Empowerment Program of PT Terminal Teluk Lamong - Tri Mega Asri; Dhita Zalzabila Angelita (Universitas Sultan Ageng Tirtayasa, 2025)
Corporate Social Responsibility (CSR) programs require systematic evaluation to ensure effective implementation and sustainable community impact. This study evaluates the Corporate Social Responsibility of PT Terminal Teluk Lamong in its MSME Canteen Empowerment Program, which began in August 2022 to support Micro, Small, and Medium Enterprises in the company's Ring I community areas. Using a qualitative descriptive research approach, data were collected through interviews with key stakeholders including the Public Relations Manager, CSR Implementation Officer, and MSME participants, supplemented by direct observation over five months (October 2022 - February 2023). The evaluation employed Stufflebeam's CIPP model (Context, Input, Process, Product) and Suharto's 4P CSR framework analyzing Profit, Planet, People, and Procedure aspects. Results demonstrate that PT Terminal Teluk Lamong allocates 2% of net profits (approximately 40 million Rupiah annually) to the MSME Canteen program. Environmental sustainability is maintained through waste segregation and collaboration with For Link Environmental Management Forum. Community empowerment shows positive economic development in Ring I areas, with MSME Canteen sales increasing from 569 packs in Q1 to 929 packs in Q3. The program includes hygiene training for 50 participants from three villages, enhancing food quality standards and business competencies. The evaluation reveals successful implementation across most criteria, with regular monitoring conducted monthly by CSR officers and quarterly by management. However, some procedural aspects require improvement, including enhanced integration with company policy and expanded partnerships with external institutions. The study concludes that the CSR program effectively contributes to community economic empowerment while maintaining environmental sustainability standards.